Development of humanities education in the context of interdisciplinary approach and informatization - Kravtsov, Yuriy S.; Oleksiuk, Mariia P.; Halahan, Ihor M.; Lehin, Viktoriia B.; Balbus, Tetiana A. (Linguistics and Culture Review, 2021)
The phenomenon of globalization is directly connected to the emergence of the global Network. National and political diversity in cyberspace fades into the background. Authenticity, self-identification of a person becomes secondary. The society determines the immersion of the individual in the virtual space and its functioning in this space. The transformation and development of humanities education is determined by the processes of informatization. The development of humanities education involves the implementation of the principle of openness of humanities education to social practices and the principle of its accessibility without age and geographical location. The introduction of info-telecommunications accelerates the creation of a single information space, provides access to the information resources. The development of humanities education is aimed at implementing an interdisciplinary approach that ensures the effectiveness of the development and application of humanitarian knowledge and form a conscious responsible choice in a variety of cultural meanings, cultural self-determination. It ensures the rigor and accuracy of the methodological and technical side of humanities education.